ANALISIS STRATEGI PELAYANAN ISLAMI DALAM MENINGKATKAN KEPUASAN PELANGGAN PADA RESTO MELITA KITCHEN - Azmi, Robet Ulil `; Ali, Misbahul; Ibrahimy, Ach. Azaim; Amir, Amir (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2025)
The market is a mechanism that can bring buyers together to make transactions on goods or services. The market is the most important part of a Muslim's life as an ideal transaction vehicle. In Indonesia the market is the economic support of society, both urban and rural communities. In terms of physical there are two types of markets in Indonesia, namely traditional markets and modern markets. Traditional market is a kind of market that is managed simply who still apply the bargaining system. While the modern market is a market that is managed with modern management that generally there dikinjagi sebaagi provider of goods or services with good quality of service to the consumer and the absence of bargaining process at the time of the transaction.Service quality is one of the fundamental parts of a growing business today. Customer satisfaction is a priority, because customers are one of the main barometers in developing a restaurant business. Keep in mind, customers are one of the valuable assets and long-term investments of a restaurant. However, along with the times, there have been many innovations related to service quality in customer satisfaction. So we need to combine the latest innovations related to service strategies in increasing customer satisfaction, within the framework of IslamThis research method is a qualitative study with a descriptive approach, which aims to describe the application of Islamic service strategies in increasing customer satisfaction at Resto Melita Kitchen, Kolor Village, Sumenep City District, Sumenep Regency. The data analysis technique used is qualitative analysis with triangulation techniques in testing the validity of the data.Based on the results of the study, the Islamic service strategy in increasing customer satisfaction at Resto Melita Kitchen, Kolor Village, Sumenep City District, Sumenep Regency is complexly contained in the SOP (Standard Operational Procedure) set by the restaurant. In the SOP (Standard Operational Procedure) there are several regulations that direct all structural managers of the restaurant to be honest, consistent, intelligent, polite and friendly to customers, responsible for the trust that has been given, maintain the quality of service and product standards, build good emotional relationships with customers and provide convenience to customers. The supporting factors for the Islamic service strategy in increasing customer satisfaction at Resto Melita Kitchen arise from the SOP (Standard Operational Procedure) that has been set by the restaurant which contains Islamic sharia values. There is training for new employees, after training there is follow-up from the leaders of each division. And employee welfare is guaranteed with a balance between the work assigned and the salary received by employees. While the inhibiting factors for the Islamic service strategy in increasing customer satisfaction at Resto Melita Kitchen arise from employees who experience underperformance and the inability of the restaurant to respond to requests from its customers. This happens due to wrong predictions or even not considering the consequences of customer satisfaction. What the researcher means is from the existence of positive viral gethok and repurchase intentions which result in over repeat orders beyond the capabilities of Resto Melita Kitchen